(untitled) (REMUNOM, 2024)
The objective of this study was to evaluate the ideal capacity of the photovoltaic system to meet the energy demand of the Tilapia Fry Production Unit in Bilene, considering load factors, solar irradiance, losses, and autonomy. The methodology involved measuring electrical parameters with a digital multimeter, analyzing the tilt angle of the solar panels, and assessing the shading of the photovoltaic modules. The results indicated power failures and current drops, attributed to improper configuration and lack of maintenance. The incorrect tilt of the panels and shading significantly affected the system’s efficiency. To maximize electrical power, it is crucial to optimize the tilt and orientation of the photovoltaic modules, especially during months of high solar radiation. The variation of voltage and power as a function of current in the photovoltaic system showed the importance of operating near the maximum power point (MPP) to maximize efficiency. The results indicate that the implementation of a photovoltaic system can improve production efficiency, reduce operating costs, and increase fry production, contributing to local food security and promoting environmental sustainability. Keywords: photovoltaic energy, fry production, energy efficiency, sustainability, food security.